2020
DOI: 10.3390/jcm9051570
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Level Is Associated with Frailty in Chronic Liver Diseases

Abstract: We sought to examine the serum zinc (Zn) level and frailty in patients with chronic liver diseases (CLDs, n = 285, 107 liver cirrhosis cases, median age = 66 years). Frailty was defined as a clinical syndrome in which three or more of the following criteria were met (frailty score 3, 4, or 5): unintentional body weight loss, self-reported exhaustion, muscle weakness (grip strength: <26 kg in men and <18 kg in women), slow walking speed (<1.0 m/s), and low physical activity. Robust (frailty score 0), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The cutoff values of CC for sarcopenia in the revised AWGS guidelines are 34 cm in males and 33 cm in females, while in our ROC analysis for frailty, the optimal cutoff values of CC were 33.7 cm in males and 33.4 cm in females, which are almost identical to AWGS data [19,34]. Sarcopenia indicates physical frailty and sarcopenia forms the basis of frailty [2,35]. Sarcopenia itself causes lower limb muscle strength, falls, slow WS, and thus, decrease in physical activity can be induced.…”
Section: Discussionsupporting
confidence: 76%
“…The cutoff values of CC for sarcopenia in the revised AWGS guidelines are 34 cm in males and 33 cm in females, while in our ROC analysis for frailty, the optimal cutoff values of CC were 33.7 cm in males and 33.4 cm in females, which are almost identical to AWGS data [19,34]. Sarcopenia indicates physical frailty and sarcopenia forms the basis of frailty [2,35]. Sarcopenia itself causes lower limb muscle strength, falls, slow WS, and thus, decrease in physical activity can be induced.…”
Section: Discussionsupporting
confidence: 76%
“…Deficiency of zinc, a cofactor in the urea cycle that metabolizes ammonium, is associated with HE, frailty, and sarcopenia in patients with cirrhosis. (19)(20)(21) Magnesium deficiency occurs because of malabsorption of magnesium in the small intestine and is exacerbated by diuretic use. Magnesium deficiency is associated with reduced cognitive performance as well as reduced muscle strength in adults with cirrhosis (22)(23)(24) and with increased bone resorption in children with cholestatic liver disease.…”
Section: Impaired Intake Of Micronutrientsmentioning
confidence: 99%
“…Some aspects regarding pathophysiological pertubations have also been depicted in patients with cirrhosis and frailty. Nishikawa and colleagues reported that the circulating levels of zinc correspond well to the aggravating frail status ranging from robustness to frailty in patients with cirrhosis, concerning zinc deficiency in close relation to various clinical symptoms like malnutrition, musculoskeletal health decline and hormonal imbalance 81 . A spectrum of hormonal changes, including decreased parathyroid hormone, testosterone, cortisol and vitamin D3, was found in patients with cirrhosis and frailty, addressing the pathway of dysregulated hormone homeostasis and consequently endocrine/metabolic dysfunction 82 .…”
Section: The Interrelation Between Frailty and Other Cirrhosis‐associ...mentioning
confidence: 99%
“…Nishikawa and colleagues reported that the circulating levels of zinc correspond well to the aggravating frail status ranging from robustness to frailty in patients with cirrhosis, concerning zinc deficiency in close relation to various clinical symptoms like malnutrition, musculoskeletal health decline and hormonal imbalance. 81 A spectrum of hormonal changes, including decreased parathyroid hormone, testosterone, cortisol and vitamin D3, was found in patients with cirrhosis and frailty, addressing the pathway of dysregulated hormone homeostasis and consequently endocrine/metabolic dysfunction. 82 Furthermore, low serum free triiodothyronine levels were associated with the presence of frailty in euthyroid patients with cirrhosis, which was independent of sodium, age and CTP classification.…”
Section: Miscellaneousmentioning
confidence: 99%